THIRD PRINCIPLE ISSUE OF FUNCTIONAL REHABILITATION: SYSTEMIC RESPONSE TO THE CHANGE OF THE ACTIVITY OF SEPARATE ACUPUNCTURAL CHANNELS AND ITS DAY'S DYNAMIC - Makats, D. (Journal of Education, Health and Sport, 2015)
Makats D. V. Third principle issue of functional rehabilitation: Systemic response to the change of the activity of separate acupunctural channels and its day's dynamic = Третє принципове питання функціональної реабілітації: Системна залежність від спрямованої активності каналів і феномен добової синхронно-асинхронної динаміки. Journal of Education, Health and Sport. 2015;5(12):177-188. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35301 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A177-188 http://pbn.nauka.gov.pl/works/679061 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 10.11.2015. Revised 25.11.2015. Accepted: 10.12.2015. УДК (UDС): 612:615,814.1 Third principle issue of functional rehabilitation: SYSTEMIC RESPONSE TO THE CHANGE OF THE ACTIVITY OF SEPARATE ACUPUNCTURAL CHANNELS AND ITS DAY'S DYNAMIC Третє принципове питання функціональної реабілітації: СИСТЕМНА заЛЕЖНІСТЬ ВІД СПРЯМОВАНОЇ активностІ каналІв І феномен ДОБОВОЇ синхронно-асинхронноЇ ДИНАМІки D. V. MAKATS Д. В. МАКАЦ Vinnytsia branch of the State enterprise of the Ukrainian scientific-research institute of transport medicine of HM of Ukraine Вінницька філія Державного підприємства Український НДІ медицини транспорту МОЗ України Abstract The following information provides the specifics of systemic dependency on the activity of separate traditional channels. Its day’s dynamics is illustrated on the example of separate functional systems. Key words: Zhenjiu therapy, acupunctural channels, functional-vegetative system of the human. Реферат Наводиться специфіка системної залежності від активності окремих традиційних каналів. Показана її добова динаміка на прикладі окремих функціональних систем. Ключові слова: Чжень-цзю терапія, акупунктурні канали, функціонально-вегетативна система людини. Реферат Рассмотрена специфика системной зависимости при возбуждении и угнетении активности отдельных акупунктурных каналов. Обращено внимание на феномен суточной синхронно-асинхронной динамики. Ключевые слова: Чжень-цзю терапия, акупунктурные каналы, функционально-вегетативная система человека.